Geringster Kabeljaubestand vor Westgrönland seit 1982 - Rätz, Hans-Joachim; Stein, Manfred (1992)
Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010